THEORETICAL FRAMEWORK OF ADMINISTRATIVE LEGAL REGULATION IN FLIGHT SAFETY AREA WITHIN CIVIL AVIATION - Pyvovar, Yuriy; Husar, Olga (Proceedings of National Aviation University, 2016)
Purpose: To define and provide general insight into theoretical legal principles of the administrative legal regulation in flight safety area within civil aviation to be used as the theoretical framework for exploring further issues in this area. Methods: The methodological framework of the study includes general scientific and special legal methods and approaches. The gnoseological approach allowed exploring the essence of the notion of flight safety area within civil aviation. The logical and semantic method helped more accurately define the notion of the administrative legal regulation in flight safety area within civil aviation. The legal analysis method contributed to exploring the normative definition of flight safety, while the comparative legal analysis contributed to doctrinally differentiating between the notion of flight safety area and the notion of flight safety. The structural and logical method allowed determining the elemental composition of the scope of the administrative legal regulation in flight safety area within civil aviation. Results: The study stresses that the modern global and national meaning of flight safety area within civil aviation requires that the area be regulated by the state, the effective system of safety assurance be generated by exercising administrative legal influence on all the elements of the area. Having analysed the normative and doctrinal definitions of the notion of flight safety area and having compared it with the notion of flight safety, we may state the first has – in its context – a broader sense than the latter, and generally constitutes the system of social relations, which arise and develop for ensuring flight safety within civil aviation and are accurately defined by laws and regulations. It is proven that one of the effective measures to ensure the operation of the said area and effectively handle challenges arising to flight safety within civil aviation is to apply administrative legal regulation in this area, which means the complicated organizational and legal system with all elements of its internal structure having the administrative legal nature and intended purposes to systemize and protect social relations in civil flight safety area. Discussion: In its strict sense, flight safety area is a phenomenon, the context of which comprises as follows: the quality of aerial transportation system determining the ability to transport by air without causing any harm to human health; legal and regulatory assurance of flight safety; the system of governmental (public) and non-governmental authorities and organisations, which control and ensure flight safety within civil aviation. It is advocated that existing and potential external and internal challenging factors, which impact the said area of the relations and – in certain cases – pose threats to and constitute weak points of this area, are integral characteristics of flight safety within civil aviation. The purpose, objectives, object, subject matter, principles, method, mechanism, and phases of the administrative legal regulation in flight safety area within civil aviation are the key elements of the context of the administrative legal regulation in civil flight safety area.